A Scalable, High‐Throughput, and Environmentally Benign Approach to Polymer Dielectrics Exhibiting Significantly Improved Capacitive Performance at High Temperatures. Issue 49 (3rd October 2018) - Zhou, Yao; Li, Qi; Dang, Bin; Yang, Yang; Shao, Tao; Li, He; Hu, Jun; Zeng, Rong; He, Jinliang; Wang, Qing
Abstract: High‐temperature capability is critical for polymer dielectrics in the next‐generation capacitors demanded in harsh‐environment electronics and electrical‐power applications. It is well recognized that the energy‐storage capabilities of dielectrics are degraded drastically with increasing temperature due to the exponential increase of conduction loss. Here, a general and scalable method to enable significant improvement of the high‐temperature capacitive performance of the current polymer dielectrics is reported. The high‐temperature capacitive properties in terms of discharged energy density and the charge–discharge efficiency of the polymer films coated with SiO2 via plasma‐enhanced chemical vapor deposition significantly outperform the neat polymers and rival or surpass the state‐of‐the‐art high‐temperature polymer nanocomposites that are prepared by tedious and low‐throughput methods. Moreover, the surface modification of the dielectric films is carried out in conjunction with fast‐throughput roll‐to‐roll processing under ambient conditions. The entire fabrication process neither involves any toxic chemicals nor generates any hazardous by‐products. The integration of excellent performance, versatility, high productivity, low cost, and environmental friendliness in the present method offers an unprecedented opportunity for the development of scalable high‐temperature polymer dielectrics. Abstract : Scalable and environmentally benign preparation of high‐performance high‐temperature dielectric polymer films is achieved by roll‐to‐roll plasma‐enhanced chemical vapor deposition (CVD) processing under room temperature and atmospheric pressure. The polymer films coated with wide‐bandgap layers exhibit high‐temperature energy‐storage capability exceeding that of state‐of‐the‐art polymer‐based dielectrics.